Al-si-cu series die-casting aluminum alloy and method for manufacturing motor end cover by using the same
Patent Information
- Application Number
- CN202611410242.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-23
AI Technical Summary
[0012]但是,上述现有技术的改性重点主要集中在一般意义上的组织细化、富铁相形貌改善、共晶组织变质或常规力学性能提升方面
本发明一种Al-Si-Cu系压铸铝合金及其制备电机端盖的方法,通过Mn、Cr、V协同作用,使Fe相关相由长针状、长条状不利形貌向短小、圆钝、珊瑚状或短棒状形貌转变,降低裂纹尖端效应;通过Zr与Er协同,并结合低温稳定化处理,在基体中形成纳米级L12型Al3(Er,Zr)核壳弥散相,提高强度并抑制热循环中的组织粗化;通过Sr对共晶Si变质,使共晶Si短纤维化,提高塑性和加工表面质量;通过分段温控、净化过滤和真空压铸,降低孔隙、夹杂和缺陷连通性,减少亚表层泄漏带形成。上述方案综合作用下,最终制得的材料能够同时获得较高的抗拉强度、较高的屈服强度、较好的伸长率、更低的加工麻点密度、更高的疲劳寿命以及更好的气密性和热循环服役稳定性,特别适用于带封闭式冷却通道且邻近区域需要精加工密封面的新能源汽车电机端盖。
Smart Images

Figure CN122959581A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alloy materials and casting technology, and more specifically, relates to an Al-Si-Cu die-cast aluminum alloy and a method for preparing motor end caps thereon. Background Technology
[0002] As new energy vehicle drive systems develop towards higher power density, higher speed, and higher integration, motor end covers have gradually evolved from traditional single enclosed support components into integrated structural components that simultaneously perform multiple functions such as cooling medium guidance, bearing support, sealing, installation connection, and localized heat dissipation. Motor end covers with enclosed cooling channels, in particular, typically integrate annular flow channels, folded flow channels, interface transition areas, flange sealing areas, and localized reinforcement structures within a limited space, placing higher demands on materials and manufacturing processes.
[0003] Currently, ADC12 aluminum alloy is widely used in automotive die-cast structural parts and housing components due to its good fluidity, excellent die-casting formability, and moderate manufacturing cost. This alloy is suitable for mass production of complex thin-walled structural parts and has high application value in ordinary motor housings, covers, and general aluminum alloy die-castings. However, when ADC12 is used to manufacture one-piece motor end caps with cooling channels, existing material systems and conventional processes are gradually revealing new limitations.
[0004] On the one hand, motor end covers with cooling channels exhibit a distinct transition between thin and thick sections. The top of the cooling channel is often a thin-walled area, while the bend and interface areas are typically connected to thick-walled flanges or mounting surfaces. This results in significant differences in local solidification conditions, easily leading to uneven microstructure, shrinkage porosity, and concentrated pores. On the other hand, the area adjacent to the cooling channel of such parts usually requires precision machining to form sealing surfaces, connecting surfaces, or cooling interface mating surfaces. Therefore, they are highly sensitive to the subsurface microstructure of the material, the integrity of the machined surface, and the airtightness stability.
[0005] For example, Chinese patent publication number CN219268609U discloses a motor rear end cover, including a body with a shaft hole and a first protruding edge circumferentially arranged around the shaft hole. A cooling groove is provided on the end face of the first protruding edge, and a liquid injection hole communicating with the cooling groove is provided on the side of the first protruding edge. A second protruding edge extends along the height direction from one side of the first protruding edge, and the second protruding edge is circumferentially arranged along the first protruding edge, with a central angle less than 360 degrees. This motor rear end cover can be connected to the motor body via the first protruding edge. The cooling groove on the first protruding edge cools the rear end cover, thereby dissipating heat from the motor shaft, while also ensuring the stability and installation accuracy of the assembly between the rear end cover and the motor body. Therefore, it can be seen that in the prior art, there are already solutions that incorporate cooling channel structures into motor end cover components to meet the heat dissipation requirements during motor operation.
[0006] Conventional ADC12 belongs to the Al-Si-Cu die-casting aluminum alloy system. To reduce the tendency of die casting sticking, the Fe content is usually relatively high. During solidification, this type of alloy easily forms needle-like or lamellar β-Al5FeSi phases, while the eutectic Si is mostly distributed in coarse lamellar or long needle-like forms, and Cu elements tend to segregate in the eutectic region. In complex structural areas with cooling channel end caps, especially in the thin-walled area at the top of the cooling channel, the turning area, and the area of adjacent sealing machined surfaces, the above-mentioned microstructure often overlaps with chain-like micropores, oxide inclusions, and local shrinkage porosity, forming continuous brittle-sensitive areas.
[0007] During the research and development process, the applicant discovered that when existing ADC12 aluminum alloy is used to manufacture integrated motor end caps with enclosed cooling channels, a subsurface brittle leakage zone is easily formed in the area adjacent to the sealing surface of the cooling channel. This zone is composed of needle-like β-Fe phase, Cu segregation eutectic structure, and chain-like micropores. After finishing, this area is prone to surface pitting, bright bands, micro-pits, and localized edge chipping. Under the coupled effects of long-term contact with coolant, temperature cycling, and motor vibration, it is also prone to inducing localized corrosion propagation, early initiation of fatigue cracks, and sealing failure.
[0008] In the existing technology, there are already schemes for microstructure modification of ADC12 or similar die-cast aluminum-silicon alloys.
[0009] For example, Chinese patent publication number CN113278831A discloses a method for preparing recycled ADC12 aluminum alloy from waste aluminum. This application improves the mechanical properties of the alloy by adding La, Ce, and Y to the recycled ADC12 system and adjusting the alloy composition with Mn and Cr, thereby improving the morphology of Fe-rich related phases and refining the eutectic structure to a certain extent.
[0010] For example, Chinese patent publication number CN111485146A discloses a high thermal conductivity, high strength, low Si cast aluminum alloy and its preparation method. This patent controls the eutectic structure and the morphology of some intermetallic compounds by setting Sr and rare earth elements, and by combining refining, slag removal and casting processes, so as to balance the thermal conductivity and mechanical properties of the alloy.
[0011] For example, Chinese patent publication number CN108034870A discloses a high-strength and high-toughness die-cast aluminum alloy and its preparation method. This application refines and modifies the grains, eutectic structure and iron-rich phase in the die-cast aluminum-silicon alloy by adding rare earth elements such as Y and Er, thereby obtaining a more uniform as-cast structure and improving the strength and toughness of the alloy.
[0012] However, the modifications in the aforementioned prior art mainly focus on general aspects such as microstructure refinement, improvement of iron-rich phase morphology, modification of eutectic structure, or enhancement of conventional mechanical properties. Regarding the technical problems already pointed out in the background section—namely, the tendency of motor end caps with enclosed cooling channels to form a subsurface brittle-sensitive region near the sealed machining surface, composed of needle-like Fe-related brittle phases, Cu segregation zones, and chain-like micropores—which further leads to increased surface pitting, bright bands, micro-pits, leakage risk, and insufficient thermal cycling stability after finishing—none of the aforementioned prior art provides targeted solutions.
[0013] Specifically, CN113278831A mainly focuses on the composition adjustment and general microstructure improvement of the recycled ADC12 system. Its disclosed content focuses on alloying treatment and conventional microstructure optimization under recycled aluminum conditions, and does not specifically address the problem of subsurface defect connectivity in complex die-cast sealing structures.
[0014] The key technology of CN111485146A is to balance thermal conductivity and strength. Its material system and application purpose are different from those of die-cast end caps with closed cooling channels. It is difficult to directly address the local brittleness sensitivity problem formed by the combination of coarse Fe-related phases, eutectic structure and pores in complex cooling channel structures.
[0015] Although CN108034870A involves the refinement and modification treatment of die-cast aluminum alloy structure by rare earth elements such as Y and Er, its disclosure mainly focuses on the improvement of the as-cast structure and mechanical properties of general die-cast aluminum alloys, and does not provide specific explanations on the airtightness stability issues related to long-term contact with coolant, thermal cycling conditions, and precision-machined sealing surfaces.
[0016] Therefore, existing technologies are not yet able to solve the aforementioned technical problems well. Summary of the Invention
[0017] To address the aforementioned problems with existing ADC12 aluminum alloys in manufacturing motor end caps with enclosed cooling channels, this invention provides an Al-Si-Cu die-cast aluminum alloy and a method for preparing motor end caps thereon. Through the synergistic effect of composition design and thermal process control, a target microstructure different from conventional ADC12 is induced within the material, thereby improving the overall service performance of motor end caps with cooling channels.
[0018] To solve the above problems, the present invention adopts the following technical solution.
[0019] An Al-Si-Cu die-cast aluminum alloy, comprising, by mass percentage: Si: 9.3%–10.2%; Cu: 1.4%–2.0%; Fe: 0.55%–0.75%; Mn: 0.65%–0.95%; Mg: 0.25%–0.40%; Cr: 0.08%–0.18%; V: 0.06%–0.16%; Zr: 0.10%–0.20%; Er: 0.04%–0.12%; Sr: 0.006%–0.015%; Ni: 0.10%–0.30%; Zn: ≤0.30%; with the balance being Al and unavoidable impurities.
[0020] Preferably, the mass percentage of Si is 9.5% to 10.0%, and this range of Si content is more conducive to obtaining a more stable eutectic Si refinement effect while ensuring fluidity.
[0021] Preferably, the mass percentage of Cu is 1.6% to 1.8%, and the mass percentage of Fe is 0.60% to 0.70%. This range of Cu and Fe content is more conducive to balancing processability and microstructure control.
[0022] Preferably, the mass percentage of Mn is 0.75% to 0.85%, the mass percentage of Cr is 0.10% to 0.15%, and the mass percentage of V is 0.08% to 0.14%. Under these ranges of Mn, Cr, and V content, the effects of shortening, rounding, and dispersing of the Fe-related phase are more stable.
[0023] Preferably, the Zr mass percentage is 0.12% to 0.18%, the Er mass percentage is 0.06% to 0.10%, and the Sr mass percentage is 0.008% to 0.012%. The Zr, Er, and Sr contents within this range are more conducive to forming a more stable nano-dispersion strengthening system and a more uniform eutectic Si refinement result.
[0024] A method for preparing motor end caps from the aforementioned Al-Si-Cu die-cast aluminum alloy includes the following steps: S1. Melt the raw materials containing Al, Si and Cu to obtain the basic melt; S2. Heat the base melt to the first temperature plateau, add Al-Zr master alloy, Al-V master alloy, and part of Al-Mn master alloy and Al-Cr master alloy, and hold at the temperature; S3. Cool the melt to the second temperature plateau, add Al-Er master alloy and the remaining Al-Mn master alloy and Al-Cr master alloy, and hold at the temperature; S4. Cool the melt to the third temperature plateau, add Sr and Mg, and hold at that temperature; S5. Degas and filter the melt; S6. Vacuum die casting is performed on the processed melt. S7. Perform low-temperature stabilization treatment on the die-cast parts. The first temperature platform is 760℃~780℃, the second temperature platform is 710℃~725℃, the third temperature platform is 675℃~690℃, and the low-temperature stabilization treatment temperature is 300℃~340℃.
[0025] Preferably, in step S1, the recycled material used accounts for 15% to 35% of the total charge, which can balance industrial economy and melt quality stability.
[0026] Preferably, the holding time in step S2 is 8–20 min, the holding time in step S3 is 10–18 min, and the holding time in step S4 is 3–8 min, so as to make the tissue precursors and degeneration processes more stable at each stage.
[0027] Preferably, in step S5, Ar gas or Ar / N2 mixed gas is used for degassing, the degassing time is 8 to 18 minutes, and ceramic filter plates with a porosity of 30 PPI to 50 PPI are used for filtration. This preferred choice of degassing and filtration process can take into account both purification effect and process feasibility.
[0028] Preferably, in step S6, the vacuum degree of vacuum die casting is no greater than 30 kPa, the low-speed injection speed is 0.2-0.8 m / s, the high-speed injection speed is 2.5-4.5 m / s, the pressurization pressure is 65-110 MPa, the mold temperature is 180℃-240℃, and the low-temperature stabilization treatment time in step S7 is 2-6 h, so as to make the die casting densification and low-temperature structure more stable.
[0029] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses an Al-Si-Cu die-cast aluminum alloy and a method for preparing motor end caps. Through the synergistic effect of Mn, Cr, and V, the Fe-related phase is transformed from unfavorable morphologies of long needles and strips to short, blunt, coral-like, or short rod-like morphologies, reducing crack tip effect. Through the synergistic effect of Zr and Er, combined with low-temperature stabilization treatment, a nanoscale L12-type Al3(Er, Zr) core-shell dispersed phase is formed in the matrix, improving strength and suppressing microstructure coarsening during thermal cycling. Through Sr modification of eutectic Si, the eutectic Si is shortened into short fibers, improving plasticity and surface finish. Through segmented temperature control, purification filtration, and vacuum die casting, porosity, inclusions, and defect connectivity are reduced, minimizing the formation of subsurface leakage zones. Under the combined effect of the above schemes, the final material can simultaneously obtain higher tensile strength, higher yield strength, better elongation, lower processing pit density, higher fatigue life, and better airtightness and thermal cycling service stability. It is particularly suitable for new energy vehicle motor end caps with closed cooling channels and adjacent areas that require precision-machined sealing surfaces. Attached Figure Description
[0030] Figure 1 The images show a comparison of the optical microstructures of the conventional ADC12 alloy and the modified alloy of Example 2. The left side shows the conventional ADC12 alloy, where the white phase is generally coarse and long strip-shaped second phases are visible in some areas. The right side shows the modified alloy of Example 2, where the microstructure is significantly refined, the coarse second phases are reduced, and the second phases exhibit a shorter and more dispersed distribution.
[0031] Figure 2 The images show a comparison of the SEM-BSE microstructures of the conventional ADC12 alloy and the modified alloy of Example 2. The left side shows the conventional ADC12 alloy, where coarser, more continuous bright white second phases can be observed in backscattered light mode, locally distributed in elongated or sheet-like patterns, and bright white phase enrichment is visible near the pores. The right side shows the modified alloy of Example 2, where the bright white second phase is significantly refined, with fewer continuous elongated morphologies, mainly exhibiting shorter, more rounded rod-like and coral-like dispersed distributions. The pore size is smaller and the distribution is more discrete.
[0032] Figure 3 This is an elemental distribution diagram of the α-Fe related phases in the modified alloy of Example 2. The diagram shows that Fe, Mn, Cr, and V co-segregate in the same region, indicating that a composite phase mainly composed of α-Al(Fe, Mn, Cr, V)Si has been formed in the modified alloy.
[0033] Figure 4The images show a comparison of the local microstructure and defect morphology of the conventional ADC12 alloy and the modified alloy of Example 2. The left side shows the conventional ADC12 alloy, where coarse Fe-related phases are distributed adjacent to pores, and there are local defect composite regions. The right side shows the modified alloy of Example 2, where the second phase is finely and dispersedly distributed, and the pores are significantly reduced and more dispersed, indicating improved local microstructure density.
[0034] Figure 5 The images show TEM, SAED, and Er and Zr elemental line scans of the modified alloy in Example 2. The images reveal nanoscale dispersed phases and corresponding diffraction characteristics. Er and Zr exhibit a core-shell distribution trend in the line scans, indicating the formation of L12-type Al3(Er, Zr) dispersed phases in the modified alloy.
[0035] Figure 6 These are comparison images of the morphology of different regions of the fatigue fracture surfaces of the conventional ADC12 alloy and the modified alloy of Example 2. Figure 6 (a) and Figure 6 (b) shows the morphology of the crack propagation zone and the final fracture zone of a conventional ADC12 alloy. Figure 6 (c) and Figure 6 (d) shows the morphology of the crack propagation zone and the final fracture zone of the modified alloy in Example 2. The fracture surface of the conventional ADC12 alloy is mainly composed of blocky fracture units and cleavage steps, and is relatively flat overall. The fracture surface of the modified alloy in Example 2 is obviously roughened, with visible tear ridges, small pits and traces of micropore aggregation, showing the characteristics of ductile fracture or mixed fracture with ductile fracture as the main feature. Detailed Implementation
[0036] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to the following embodiments. Equivalent substitutions or modifications made by those skilled in the art without departing from the spirit and essence of the present invention should fall within the protection scope of the present invention.
[0037] An Al-Si-Cu die-cast aluminum alloy, comprising, by mass percentage: Si: 9.3%–10.2%; Cu: 1.4%–2.0%; Fe: 0.55%–0.75%; Mn: 0.65%–0.95%; Mg: 0.25%–0.40%; Cr: 0.08%–0.18%; V: 0.06%–0.16%; Zr: 0.10%–0.20%; Er: 0.04%–0.12%; Sr: 0.006%–0.015%; Ni: 0.10%–0.30%; Zn: ≤0.30%; with the balance being Al and unavoidable impurities.
[0038] Among them, Si is used to ensure fluidity and filling capacity, and serves as the basis for regulating eutectic structure; Cu is used to maintain matrix strength; Fe is used to maintain the basic conditions required for die casting demolding process; Mn, Cr, and V are used to regulate the morphology and type of Fe-related phases; Zr and Er are used to construct a nanoscale dispersion strengthening system; Sr is used to change the growth mode of eutectic Si; Mg and Ni are used to participate in matrix strengthening and thermal stability improvement. Each element does not act independently, but rather influences the microstructure evolution path through compositional coupling and subsequent process coordination.
[0039] The preferred range for the mass percentage of Si is 9.5% to 10.0%. When Si is below this preferred range, the filling capacity of thin-walled die castings and complex flow channels will decrease, and the uniformity of local microstructure will also be affected. When Si is above this preferred range, the tendency for eutectic Si coarsening is enhanced, and even with subsequent modification with Sr, longer eutectic Si phases may still form locally, affecting plasticity and surface finish. Therefore, a Si content of 9.5% to 10.0% is more conducive to achieving a more stable eutectic Si refinement effect while ensuring fluidity.
[0040] The preferred mass percentage range for Cu is 1.6%–1.8%, and for Fe is 0.60%–0.70%. When Cu is below 1.6%, the matrix strengthening effect is insufficient, resulting in limited improvement in tensile strength and yield strength. When Cu is above 1.8%, Cu segregation in the eutectic region and residual liquid phase is more pronounced, which is detrimental to local electrochemical homogeneity in the coolant environment and also increases subsurface brittleness sensitivity. When Fe is below 0.60%, although the tendency for coarse Fe-related phases to form can be further reduced, the anti-sticking stability in the die-casting process will be weakened. When Fe is above 0.70%, the risk of re-increase in elongated or continuous Fe-related phases increases significantly. Therefore, the aforementioned preferred ranges for Cu and Fe are more conducive to balancing processability and microstructure control.
[0041] The preferred mass percentage ranges for Mn are 0.75%–0.85%, for Cr 0.10%–0.15%, and for V 0.08%–0.14%. Mn, Cr, and V are key components for reconstructing the morphology of Fe-related phases. When Mn is too low, the driving force for the transformation of the Fe phase from the β phase to the α phase is insufficient; when Cr is too low, the effects of shortening and rounding the Fe phase are unstable; and when V is too low, the role of high-temperature precursor formation is insufficient. However, if the contents of these three components are too high, the number of locally complex intermetallic compounds will increase, the strengthening effect will tend to saturate, and it may adversely affect plasticity and surface workability. Therefore, the above preferred ranges correspond to the intervals where the effects of shortening, rounding, and dispersing the Fe-related phases are relatively stable.
[0042] The preferred mass percentage ranges for Zr are 0.12%–0.18%, for Er 0.06%–0.10%, and for Sr 0.008%–0.012%. Zr and Er jointly participate in the formation and precipitation of the precursor of the nanoscale dispersed strengthening phase. When the contents of both are too low, the number of nanoscale dispersed phases formed during subsequent low-temperature stabilization treatment is insufficient; when the contents of both are too high, although the strengthening effect can be improved, the microstructure regulation tends to saturate, and the improvement in plasticity decreases. When Sr is too low, the eutectic Si modification effect is insufficient; when Sr is too high, it is easy to cause over-modification or local microstructure instability. Therefore, the above-mentioned preferred ranges are more conducive to forming a more stable nanoscale dispersed strengthening system and a more uniform eutectic Si refinement result.
[0043] The preparation method of this Al-Si-Cu die-cast aluminum alloy includes the following steps.
[0044] S1. Weigh out industrial pure aluminum, Al-Si master alloy, Al-Cu master alloy, and recycled materials according to the design proportions. The recycled materials are reusable metal materials generated during the smelting, die-casting, gating and riser removal, machining, or trial production of similar or related Al-Si-Cu die-cast aluminum alloys. These mainly include runner material, scrap, trimmed material, and screened reclaimed material. Before adding these materials, they must be degreased, dehydrated, and surface-oxidized to reduce oil, moisture, scale, and other inclusions introduced into the melt, thus minimizing gas absorption, inclusions, and compositional fluctuations during the smelting process. Add all raw materials to the smelting furnace and perform initial melting at 700℃~735℃ to obtain the basic Al-Si-Cu melt.
[0045] In this step, recycled material accounts for 15% to 35% of the total charge. Too low a proportion of recycled material increases material costs and hinders industrial implementation; too high a proportion introduces more oxide inclusions, compositional fluctuations, and inherited microstructures, reducing melt cleanliness and process stability. Therefore, a range of 15% to 35% balances industrial economics with melt quality stability.
[0046] S2. Heat the melt to 760℃~780℃, preferably 765℃~775℃. Add Al-Zr master alloy, Al-V master alloy, and 40%~70% of Al-Mn master alloy and Al-Cr master alloy in total at this temperature plateau, hold for 8~20 min, preferably 10~15 min, while stirring at low intensity.
[0047] S3. Cool the melt to 710℃~725℃, preferably 715℃~722℃. Add Al-Er master alloy and the remaining Al-Mn master alloy and Al-Cr master alloy to this temperature plateau, and hold for 10~18 min, preferably 10~12 min.
[0048] S4. Cool the melt to 675℃~690℃, preferably 678℃~685℃. Add Sr modifier and Mg master alloy to this temperature plateau and hold for 3~8 min, preferably 4~6 min.
[0049] S5. After step S4, allow the mixture to stand and remove slag, then perform rotary degassing. The degassing gas is preferably Ar or an Ar / N2 mixture, the rotor speed is 250–450 rpm, and the degassing time is 8–18 min. After degassing, use a 30–50 PPI ceramic foam filter plate for online filtration, and transfer the melt to a holding furnace at 640℃–680℃. The holding time is preferably no more than 120 min.
[0050] Insufficient degassing time results in limited reduction in hydrogen content and a significant number of microporous defects; excessive degassing time reduces process efficiency and increases melt heat exposure. If the filter plate porosity is too low, its ability to remove fine inclusions is insufficient; if the porosity is too high, it easily leads to increased filtration resistance and decreased industrial implementation stability. Therefore, the above ranges are used to balance purification effectiveness and process feasibility.
[0051] S6. The motor end cap with cooling channels is formed using vacuum die casting. The vacuum level is preferably ≤30 kPa absolute pressure, more preferably ≤20 kPa absolute pressure; the low-speed injection speed is 0.2~0.8 m / s, the high-speed injection speed is 2.5~4.5 m / s, the boosting pressure is 65~110 MPa, and the mold temperature is 180℃~240℃. For the thin-walled area at the top of the cooling channel and the turning area, local thermal balance and local cooling control are preferably set.
[0052] S7. After the die-casting process, the castings are degated and cleaned, and then subjected to low-temperature stabilization treatment at 300℃~340℃ for 2~6 hours, preferably at 315℃~325℃ for 3~5 hours. If the low-temperature stabilization treatment time is insufficient, the precipitation of nano-scale dispersed phases will be inadequate; if the time is too long, the strengthening effect will tend to saturate and the efficiency will decrease.
[0053] After low-temperature stabilization treatment, the workpiece undergoes further finishing processes to form the final complete product.
[0054] By employing the above-described composition design and preparation method, a motor end cover with a closed cooling channel that exhibits excellent performance and meets usage requirements can be produced. It should be noted that the performance optimization of this invention does not stem from the design of a single element or preparation method, but rather from the combined effect of synergistic composition design and a staged temperature control process.
[0055] By distributing different elements to different temperature platforms and controlling their dissolution, segregation, nucleation, and precipitation processes under purification, vacuum die casting, and low-temperature stabilization conditions, the alloy microstructure evolves along a path different from that of conventional ADC12, ultimately forming a hierarchical composite microstructure characterized by short, rounded Fe-related composite phases, refined eutectic Si, nanoscale dispersed strengthening phases, and low-connectivity porous structures. This microstructure directly corresponds to the comprehensive improvement in strength, plasticity, fatigue life, surface integrity, airtightness, and thermal cycling stability achieved by this invention. The specific mechanism evolution process of this invention will be described in detail below.
[0056] In the initial melting stage, pure aluminum, Al-Si master alloy, Al-Cu master alloy, and recycled materials are melted at 700℃~735℃. This primarily serves to establish a relatively homogeneous basic melt state and mitigate the influence of local segregation and inherited structures in the original materials. If the initial melting temperature is too low, the master alloy will not dissolve sufficiently, resulting in uneven distribution of elements in the melt and the potential formation of coarse second phases or segregation zones in certain areas. Conversely, if the initial melting temperature is too high, gas absorption and oxidation in the melt will intensify, hindering subsequent defect control.
[0057] Therefore, the technical effect of this stage is to provide melt conditions with uniform composition and low oxidation level for subsequent staged temperature control, thereby improving the repeatability and stability of microstructure regulation from the source.
[0058] At the first temperature plateau, the melt is heated to 760℃~780℃ and Al-Zr master alloy, Al-V master alloy, and parts of Al-Mn master alloy and Al-Cr master alloy are added. The core function of this step is to construct a high-temperature precursor environment and preemptively alter the formation conditions of Fe-related phases. Zr and V are more readily dissolved and form stable enriched regions at high temperatures; these enriched regions can serve as precursor nuclei for the subsequent formation of dispersion-strengthening phases. The partial addition of Mn and Cr at this stage allows them to enter the local chemical environment before the formation of Fe-related phases, reducing the tendency for Fe to directly form elongated or flaky β-Al5FeSi phases at the end of solidification.
[0059] Therefore, the technical effects of this step are: first, it establishes a precursor foundation for the subsequent formation of nanoscale dispersed strengthening phases; second, it preemptively weakens the formation tendency of coarse, continuous Fe-related phases; and third, it creates conditions for segregation and morphology reconstruction in the subsequent second temperature plateau. From the perspective of final performance, this step helps reduce the number of coarse, brittle second phases, reduces crack initiation sources, and lays the foundation for subsequent improvements in strength and fatigue performance.
[0060] At the second temperature plateau, after the melt is cooled to 710℃~725℃, Al-Er master alloy and the remaining Al-Mn and Al-Cr master alloys are added. This step is a key stage in the microstructure control of this invention, and its role is to complete the dispersion-strengthening phase precursor segregation and Fe-related phase morphology reconstruction. Within this temperature range, the overall diffusion capacity of the melt is reduced compared to the higher temperature stage, while the driving force for local segregation is enhanced. Er is more likely to segregate near the Zr / V-rich precursor region formed at the first temperature plateau, forming a favorable precursor structure for subsequent nano-dispersed phase precipitation; at the same time, the remaining Mn and Cr continue to participate in the adjustment of the local composition environment of the Fe-related phase, making Fe more inclined to form short, blunt, coral-like or short rod-shaped α-Al(Fe,Mn,Cr,V)Si composite phases during solidification, rather than forming continuously growing β-Al5FeSi phases.
[0061] Therefore, the technical effects of this step are: 1. It transforms the unfavorable elongated continuous morphology of the Fe-related phase into a short, dispersed, and rounded morphology; 2. It establishes an Er-rich and Zr-rich precursor region for the precipitation of nanoscale dispersed strengthening phases in subsequent low-temperature stabilization treatment; 3. It reduces the possibility of coarse Fe phases coupling with pores to form continuous brittle pathways. As a result, the crack propagation resistance of the material is increased, the fracture mode changes from brittle to ductile or mixed fracture, and fatigue life and fracture reliability are improved.
[0062] At the third temperature plateau, Sr and Mg are added after the melt is cooled to 675℃~690℃. This step mainly completes the eutectic Si modification and stabilizes the melt state before casting. Sr can change the growth mode of eutectic Si during solidification, transforming it from coarse lamellar, needle-like, or lath-like structures to short fibrous and granular chains, thereby reducing the length and sharpness of the Si phase. The addition of Mg in this temperature range helps to reduce burn-off and ensure effective retention.
[0063] The technical effects of this step are: 1. Reducing local brittleness and the tendency for micro-scraping during processing caused by coarse eutectic Si; 2. Improving matrix continuity and slowing down the rapid propagation of cracks along the eutectic region; 3. Improving the surface quality of the sealed surface and reducing pitting, bright bands, and micro-craters. Therefore, the third temperature plateau mainly corresponds to improved plasticity, enhanced surface integrity, and improved sealing surface quality.
[0064] Following the third temperature plateau, static slag removal, rotary degassing, and ceramic filtration are performed. This step serves not only to reduce the hydrogen and inclusion content in the melt but also to control the formation of porosity defects and their coupling with the second phase. In conventional ADC12, insufficient melt cleanliness easily leads to the formation of chain-like micropores and inclusion-porosity composite defects in the residual liquid phase enrichment zone, the Fe-related phase adjacency zone, and the thick-thickness transition zone. Once these defects couple with the coarse second phase, they easily form a subsurface leakage zone after finishing. Rotary degassing reduces the number of micropore nuclei, and ceramic filtration removes larger oxide inclusions and unstable particles.
[0065] Therefore, the technical effects of this step are: 1. reducing the number of pores; 2. reducing pore connectivity; 3. reducing inclusion-induced defect complexes; and 4. reducing the possibility of defects and brittle second phases forming continuous leakage channels. As a result, the material's airtightness, leakage resistance, and long-term service stability of cooling channels are significantly improved.
[0066] In the vacuum die casting stage, low-entrapment gas filling, high-pressure forming, and local thermal balance control work together to optimize the microstructure and defect state. Vacuum die casting can reduce the degree of gas entrapment during high-speed filling and reduce gas-filled porosity; high-pressure filling and pressurization processes help refine the microstructure and reduce shrinkage porosity and pore connectivity; local thermal balance control of the thin-walled area at the top of the cooling channel, the turning area, and the adjacent thick-walled area can reduce the differences in solidification behavior between different regions and reduce local liquid phase retention and defect accumulation in the thick-thin transition zone.
[0067] Therefore, the technical effects of this step are: 1. Obtaining a denser die-cast microstructure; 2. Reducing porosity and shrinkage tendency in the vicinity of the cooling channel; 3. Suppressing the formation of subsurface defect networks; 4. Improving the service stability of the end cap sealing area and the cooling channel area. Furthermore, the rapid solidification of vacuum die casting allows the α-Al matrix to retain a certain degree of supersaturated solute state, providing a basis for precipitation strengthening during low-temperature stabilization treatment.
[0068] After die casting, the casting undergoes a low-temperature stabilization treatment at 300℃~340℃. The purpose is not traditional high-temperature solution treatment, but rather to promote the precipitation and stable existence of a nanoscale dispersed strengthening phase by utilizing the supersaturated solute state of the die-cast matrix, while avoiding bubbling and dimensional instability. During this process, Er preferentially participates in the formation of nanoscale ordered precipitate nuclei, while Zr accumulates around them, thus forming an L12-type Al3(Er,Zr) dispersed phase with Er-rich nuclei and Zr-rich shells. This type of dispersed phase is small in size and widely distributed, effectively pinning dislocations and inhibiting microstructure coarsening, while avoiding the plasticity loss caused by coarse and brittle phases.
[0069] Therefore, the technical effects of this step are: 1. Increased tensile strength and yield strength; 2. Improved microstructural stability and strength retention after thermal cycling; 3. Reduced residual stress in the thin-thickness transition zone; 4. Improved dimensional stability and service stability of the sealing surface. From a long-term service perspective, low-temperature stabilization treatment can reduce dimensional changes during thermal cycling, decrease leakage rate, and extend fatigue life.
[0070] The preparation method of this invention limits the holding time for each of the three temperature plateaus to ensure greater stability of the tissue precursors and metamorphic processes at each stage. Specifically, a holding time that is too short for the first temperature plateau is detrimental to the complete dissolution of Zr and V and the formation of high-temperature precursor nuclei; while a holding time that is too long increases the risk of gas uptake and oxidation. A holding time that is too short for the second temperature plateau is detrimental to Er segregation and the continued participation of Mn and Cr in local component reconstruction; while a holding time that is too long reduces efficiency and increases unnecessary heat exposure. A holding time that is too short for the third temperature plateau makes it difficult to stably establish Sr metamorphism; while a holding time that is too long may cause Sr degradation.
[0071] Through the synergistic effect of the above steps, the alloy of the present invention ultimately forms the following hierarchical composite structure: The Fe-related phase changes from a long strip, needle-like, and continuous distribution to a short, rounded, coral-like, or short rod-like dispersed distribution; the eutectic Si changes from a coarse sheet and long needle-like structure to a short fiber and granular chain structure; a nanoscale L12-type Al3(Er,Zr) dispersed phase is formed in the matrix; and the pores change from an easily connected state to a fine, discrete, and poorly connected state.
[0072] The technical effects of the aforementioned structure are as follows: after the reduction of coarse, continuous, brittle phases, the local stress concentration of the material is weakened, and the tensile strength and yield strength are improved; after the eutectic Si and Fe-related phases are refined and passivated, crack initiation and propagation are hindered, and the elongation and fatigue life are improved; after the pore connectivity is reduced, the tendency to form subsurface leakage zones is weakened, and the airtightness and anti-leakage ability are improved; after the formation of nanoscale dispersed strengthening phases, the structural stability and dimensional retention ability during thermal cycling are enhanced; after the structural homogenization and the reduction of defects, the local electrochemical inhomogeneity in the coolant environment is reduced, and the corrosion resistance is improved.
[0073] Therefore, the process of the present invention not only changes the microstructure, but also achieves a comprehensive improvement in strength, plasticity, surface quality, fatigue life, airtightness, corrosion resistance and thermal cycling stability through the reconstruction of the microstructure evolution path.
[0074] The technical effects of the present invention will be further illustrated below through specific embodiments and comparative examples.
[0075] In the examples and comparative examples, the raw materials used included industrial pure aluminum ingots, Al-Si master alloys, Al-Cu master alloys, Al-Mn master alloys, Al-Cr master alloys, Al-V master alloys, Al-Zr master alloys, Al-Er master alloys, Al-Sr master alloys, Al-Mg master alloys, and Al-Ni master alloys. The top wall thickness of the cooling channel in the final product was 3.2–4.0 mm, and the flange area thickness was 6.0–7.5 mm.
[0076] Specific testing items include optical metallographic observation, SEM-BSE microstructure observation, EDS surface distribution analysis, TEM and SAED analysis, room temperature tensile property testing, surface roughness and pit density statistics of sealing surfaces, fatigue life testing, helium mass spectrometry leakage testing after thermal cycling, electrochemical corrosion testing in coolant environment, and dimensional change testing before and after thermal cycling.
[0077] The test specimens consist of at least 5 tensile specimens per group, at least 6 fatigue specimens per group, and at least 10 leakage test specimens per group. In the table, the relative leakage rate is defined as the ratio of the average leakage rate of each specimen after 100 thermal cycles to the corresponding average leakage rate of Comparative Example 1; the relative corrosion current is defined as the ratio of the average corrosion current density of each specimen to the average value of Comparative Example 1; and the relative dimensional change is defined as the ratio of the average dimensional change of each specimen after thermal cycles to the average value of Comparative Example 1. Therefore, all three relative values for Comparative Example 1 are set to 1.00.
[0078] Example 1: Alloy composition (mass percentage): Si 9.30, Cu 1.40, Fe 0.55, Mn 0.65, Mg 0.25, Cr 0.08, V 0.06, Zr 0.10, Er 0.04, Sr 0.006, Ni 0.10, balance Al and unavoidable impurities.
[0079] Process conditions: initial melting temperature 720℃; first temperature plateau 770℃, held for 12 min; second temperature plateau 718℃, held for 12 min; third temperature plateau 682℃, held for 5 min; degassing for 12 min; rotor speed 350 rpm; filter plate 40 PPI; vacuum degree 18 kPa; low-speed injection 0.4 m / s; high-speed injection 3.4 m / s; booster pressure 92 MPa; mold temperature 205℃; low-temperature stabilization treatment 320℃×4 h.
[0080] Organization and Effects: This embodiment produces a more noticeably refined microstructure. Compared to Comparative Example 1, the coarse, bright white second phase is reduced, the continuous bright white phase is significantly weakened, and the coupling phenomenon between local defects and the second phase is alleviated. Due to the key elements being at their lower limits, the number of nano-dispersed phases is relatively small, and the passivation degree of the Fe phase and the improvement in overall performance are lower than in Example 2, but significantly better than in Comparative Example 1.
[0081] Example 2: Alloy composition (mass percentage): Si 9.75, Cu 1.70, Fe 0.65, Mn 0.80, Mg 0.32, Cr 0.13, V 0.11, Zr 0.15, Er 0.08, Sr 0.010, Ni 0.20, balance Al and unavoidable impurities.
[0082] Process conditions: initial melting temperature 720℃; first temperature plateau 770℃, held for 12 min; second temperature plateau 718℃, held for 12 min; third temperature plateau 682℃, held for 5 min; degassing for 12 min; rotor speed 350 rpm; filter plate 40 PPI; vacuum degree 18 kPa; low-speed injection 0.4 m / s; high-speed injection 3.4 m / s; booster pressure 92 MPa; mold temperature 205℃; low-temperature stabilization treatment 320℃×4 h.
[0083] Organization and Effects Description: (e.g.) Figure 1 As shown, the overall microstructure of Example 2 is significantly finer than that of Comparative Example 1, with a reduction in coarse second phase. Figure 2 As shown, the bright white second phase changes from a coarser, more continuous morphology to a shorter, more rounded, and more diffuse distribution. For example... Figure 3 As shown, Fe, Mn, Cr, and V co-segregate in the same region, indicating the formation of a composite phase dominated by α-Al(Fe,Mn,Cr,V)Si. Figure 4 As shown, the local density of the microstructure is increased, and the phenomenon of composite distribution of pores and the second phase is significantly weakened. For example... Figure 5 As shown, nanoscale dispersed phases exist in the matrix, with Er and Zr exhibiting a core-shell distribution trend. Figure 6 (c) Figure 6 As shown in (d), the fracture surface is significantly roughened, exhibiting characteristics of ductile fracture or a mixed fracture dominated by ductile fracture.
[0084] This embodiment achieves a good balance between microstructure optimization, strength, plasticity, fatigue life, leakage rate, corrosion resistance and thermal cycling dimensional stability, and is the most preferred embodiment.
[0085] Example 3: Alloy composition (mass percentage): Si 10.20, Cu 2.00, Fe 0.75, Mn 0.95, Mg 0.40, Cr 0.18, V 0.16, Zr 0.20, Er 0.12, Sr 0.015, Ni 0.30, balance Al and unavoidable impurities.
[0086] Process conditions: Same as in Example 2.
[0087] Organization and Effects Description: In this embodiment, the Fe-related phase still predominates in a relatively short and rounded morphology, while the number of nano-dispersed reinforcing phases further increases, resulting in a higher degree of matrix reinforcement. Compared to Example 2, the strength is further improved, but the improvement in plasticity is slightly reduced, indicating that when multiple reinforcing elements approach their upper limit, the strengthening effect intensifies while the improvement in plasticity tends to plateau.
[0088] Example 4: Alloy composition (mass percentage): Same as Example 2.
[0089] Process conditions: initial melting temperature 700℃; first temperature plateau 760℃, holding for 8 min; second temperature plateau 710℃, holding for 10 min; third temperature plateau 675℃, holding for 3 min; degassing for 8 min; rotor speed 250 rpm; filter plate 30 PPI; vacuum degree 30 kPa; low-speed injection 0.2 m / s; high-speed injection 2.5 m / s; booster pressure 65 MPa; mold temperature 180℃; low-temperature stabilization treatment 300℃×2 h.
[0090] Organization and Effects Description: This embodiment can form the target structure of the present invention, but the Zr and V precursor construction and Er segregation are relatively weak, the eutectic Si refinement and low temperature stabilization effects are lower than those of Example 2, and the overall performance is lower than that of Example 2, but it is still significantly better than Comparative Example 1.
[0091] Example 5: The alloy composition and process conditions are the same as in Example 2.
[0092] Organization and Effects Description: This embodiment is used to verify the repeatability of the preferred solution described in Example 2. Its organizational morphology and performance results are basically consistent with those of Example 2, indicating that the preferred solution of the present invention has good process stability and repeatability.
[0093] Example 6: Alloy composition (mass percentage): Same as Example 2.
[0094] Process conditions: initial melt temperature 735℃; first temperature plateau 780℃, holding for 20 min; second temperature plateau 725℃, holding for 18 min; third temperature plateau 690℃, holding for 8 min; degassing for 18 min; rotor speed 450 rpm; filter plate 50 PPI; vacuum degree 20 kPa; low-speed injection 0.8 m / s; high-speed injection 4.5 m / s; booster pressure 110 MPa; mold temperature 240℃; low-temperature stabilization treatment 340℃×6 h.
[0095] Organization and Effects Description: This embodiment can still form the hierarchical composite structure of the present invention, but the organization control tends to be saturated, and the improvement in local plasticity and surface quality is slightly lower than that of Embodiments 2 and 5.
[0096] Comparative Example 1: Using conventional ADC12, the alloy composition (mass percentage) is: Si 10.60, Cu 2.40, Fe 0.95, Mn 0.20, Mg 0.15, Cr 0.02, V 0, Zr 0, Er 0, Sr 0, Ni 0.08, with the balance being Al and unavoidable impurities.
[0097] Process conditions: Conventional smelting and die casting processes are used, without staged temperature control feeding, without adding Zr, Er, V, or Sr, and without low-temperature stabilization treatment.
[0098] Organization and Effects Description: This comparative example contains a relatively coarse and continuous bright white second phase, with obvious coupling between the pores and the second phase. Figure 1 The white mask shown on the left is relatively thick overall; Figure 2 The left side shows a bright white second phase that grows continuously and is significantly enriched near the pores; Figure 4 On the left, coarse second phase is visible, distributed adjacent to pores, forming a defect complex zone; Figure 6 (a) Figure 6 (b) The fracture surface shows that brittle fracture is dominant. This comparative example serves as the benchmark for comparing various relative values and performance.
[0099] Comparative Example 2: Alloy composition (mass percentage): Based on Example 2, only Fe was adjusted to 0.90%, and the remaining composition was the same as in Example 2.
[0100] Process conditions: Same as in Example 2.
[0101] Reasons and results of the comparison: This was used to verify the importance of the upper limit of Fe. The results showed a significant increase in coarse, continuous Fe-related phases, a resurgence of elongated bright white phases under SEM-BSE, a decrease in fatigue life, and an increase in leakage rate after thermal cycling. This indicates that excessive Fe levels weaken the effects of shortening and dispersing Fe-related phases.
[0102] Comparative Example 3: Alloy composition (mass percentage): Based on Example 2, only Mn, Cr, and V were adjusted to 0.30%, 0.03%, and 0%, respectively, while the remaining composition was the same as in Example 2.
[0103] Process conditions: Same as in Example 2.
[0104] Reasons and results of the comparison: This study was used to verify the necessity of the synergistic combination of Mn, Cr, and V. The results showed insufficient passivation of the Fe-related phase and enhanced continuity of the bright white second phase, indicating that when Mn, Cr, and V are insufficient, the transformation of the Fe-related phase from the β phase to the short, rounded α phase is difficult to fully proceed.
[0105] Comparative Example 4: Alloy composition (mass percentage): Based on Example 2, Zr and Er were removed, and the remaining composition was the same as in Example 2.
[0106] Process conditions: Same as in Example 2.
[0107] Reasons and results of the comparison: This study was used to verify the effects of Zr and Er on nano-dispersion strengthening systems. The results showed that it was difficult to observe obvious core-shell nano-dispersion phases in TEM, and the strength and thermal cycling dimensional stability were significantly reduced, indicating that it is necessary for Zr and Er to synergistically construct a dispersion strengthening phase system.
[0108] Comparative Example 5: Alloy composition (mass percentage): Based on Example 2, Sr was removed, and the remaining composition was the same as in Example 2.
[0109] Process conditions: Same as in Example 2.
[0110] Reasons and results of the comparison: This study aimed to verify the role of Sr in the modification of eutectic Si. The results showed that the eutectic Si refinement was insufficient, and the pit density increased significantly after machining, indicating that Sr plays a crucial role in improving surface integrity.
[0111] Comparative Example 6: Alloy composition (mass percentage): Same as Example 2.
[0112] Process conditions: Instead of using staged temperature control and feeding, all alloying elements are added at around 740℃ in one go, followed by direct degassing and die casting; the rest of the process is as consistent as possible with Example 2.
[0113] Reasons and results of the comparison: This was used to verify the necessity of staged feeding. Results showed decreased microstructure uniformity and weakened control over Fe phase morphology. Figure 2 The reduced proportion of short, dispersed second phases indicates that staged feeding is an important process condition for constructing precursors and optimizing Fe-related phases.
[0114] Comparative Example 7: Alloy composition (mass percentage): Same as Example 2.
[0115] Process conditions: The staged temperature-controlled feeding method of Example 2 is adopted, but the ceramic filter is cancelled and non-vacuum die casting is used.
[0116] Reasons for comparison and results: This method was used to verify the effects of purification filtration and vacuum die casting. The results showed a significant increase in the number of pores and the degree of connectivity, intensified coupling between local defects and the second phase, and a significant increase in leakage rate, indicating that purification filtration and vacuum die casting jointly reduce defect connectivity.
[0117] Comparative Example 8: Alloy composition (mass percentage): Same as Example 2.
[0118] Process conditions: The process of Example 2 is used, but the low-temperature stabilization treatment of 300℃~340℃ is not performed after die casting.
[0119] Reasons for comparison and results: This study was used to verify the necessity of low-temperature stabilization treatment. The results showed that the dimensional change increased and the strength retention decreased after thermal cycling, indicating that low-temperature stabilization treatment plays an important role in improving the precipitation of nano-dispersed phases and thermal cycling stability.
[0120]
[0121]
[0122] As shown in Tables 1 and 2, compared with Comparative Example 1, the embodiments of the present invention have significant improvements in tensile strength, yield strength, elongation, surface roughness, pit density, fatigue life, relative value of leakage rate, relative value of corrosion current, and relative value of dimensional change. This indicates that the present invention can effectively improve the microstructure of the ADC12 system and enhance its overall performance through component synergistic design and staged temperature control process.
[0123] From the examples of the component endpoints, Examples 1, 2, and 3 correspond to the lower limit, middle value, and upper limit of the component range, respectively, and all three are superior to Comparative Example 1, indicating that the component range defined by the claims is feasible overall. Among them, Example 2 has a more balanced overall performance, Example 3 has higher strength but slightly lower elongation, and Example 1 shows that it can still achieve significantly better performance than conventional ADC12 when the component is at the lower limit.
[0124] From the process endpoint examples, Examples 4, 5, and 6 correspond to the lower limit, intermediate value, and upper limit of the key process parameters, respectively. All three are superior to Comparative Example 1, indicating that the process parameter range defined by the present invention is generally feasible. Among them, Example 5 has the best overall performance, indicating that the intermediate value process conditions are more conducive to forming a stable and balanced tissue state. Examples 4 and 6 respectively demonstrate that the target tissue of the present invention can still be formed when the process parameters are at the lower limit or the upper limit, but the overall performance is slightly lower than that of the intermediate value process examples.
[0125] The comparative examples show that: Comparative Example 2 indicates that when the Fe content exceeds the scope of this invention, the tendency for coarse, continuous Fe-related phases to form increases, and the overall performance decreases; Comparative Example 3 indicates that when the synergy of Mn, Cr, and V is insufficient, the effect of Fe-related phase morphology control weakens; Comparative Example 4 indicates that after removing Zr and Er, the dispersion strengthening and thermal cycling stability improvement are insufficient; Comparative Example 5 indicates that after removing Sr, the eutectic Si refinement is insufficient, and the surface quality deteriorates; Comparative Example 6 indicates that when staged feeding is not used, the microstructure control and performance improvement are insufficient; Comparative Example 7 indicates that after removing filtration and using non-vacuum die casting, the defect connectivity increases, and the fatigue performance and airtightness decrease; Comparative Example 8 indicates that when low-temperature stabilization treatment is not performed, the thermal cycling dimensional stability and leakage performance improvement are insufficient.
[0126] In summary, the results shown in Tables 1 and 2 demonstrate that the present invention can not only improve strength, but also simultaneously improve plasticity, surface quality, fatigue life, airtightness, corrosion resistance, and dimensional stability during thermal cycling.
[0127] In summary, this invention, through compositional reconstruction of the ADC12 alloy and combined with staged temperature-controlled melting, purification filtration, vacuum die casting, and low-temperature stabilization treatment, successfully constructed a hierarchical composite microstructure within the material. This microstructure consists of nanoscale L12-type Al3(Er,Zr) dispersed phases, short rod-shaped and coral-like α-Al(Fe,Mn,Cr,V)Si phases, short fibrous eutectic Si, and a low-connectivity porous structure. This microstructure significantly weakens the subsurface brittle leakage zone in conventional ADC12, which is composed of needle-like Fe-related phases, Cu segregation regions, and chain-like micropores. This results in significant improvements in the material's strength, plasticity, fatigue life, surface finish, airtightness, corrosion resistance, and thermal cycling stability.
[0128] The above embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Equivalent substitutions or modifications made by those skilled in the art without departing from the spirit and substance of the present invention should fall within the scope of protection of the present invention.
Claims
1. An Al-Si-Cu die-cast aluminum alloy, characterized in that, By mass percentage, it includes: Si: 9.3%–10.2%; Cu: 1.4%–2.0%; Fe: 0.55%–0.75%; Mn: 0.65%–0.95%; Mg: 0.25%–0.40%; Cr: 0.08%–0.18%; V: 0.06%–0.16%; Zr: 0.10%–0.20%; Er: 0.04%–0.12%; Sr: 0.006%–0.015%; Ni: 0.10%–0.30%; Zn: ≤0.30%; the balance being Al and unavoidable impurities.
2. The Al-Si-Cu die-cast aluminum alloy according to claim 1, characterized in that, The mass percentage of Si is 9.5% to 10.0%.
3. The Al-Si-Cu die-cast aluminum alloy according to claim 1, characterized in that, The mass percentage of Cu is 1.6% to 1.8%, and the mass percentage of Fe is 0.60% to 0.70%.
4. The Al-Si-Cu die-cast aluminum alloy according to claim 1, characterized in that, The mass percentage of Mn is 0.75% to 0.85%, the mass percentage of Cr is 0.10% to 0.15%, and the mass percentage of V is 0.08% to 0.14%.
5. The Al-Si-Cu die-cast aluminum alloy according to claim 1, characterized in that, The Zr mass percentage is 0.12% to 0.18%, the Er mass percentage is 0.06% to 0.10%, and the Sr mass percentage is 0.008% to 0.012%.
6. A method for preparing motor end caps from Al-Si-Cu die-cast aluminum alloy according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Melt the raw materials containing Al, Si and Cu to obtain the basic melt; S2. Heat the base melt to the first temperature plateau, add Al-Zr master alloy, Al-V master alloy, and part of Al-Mn master alloy and Al-Cr master alloy, and hold at the temperature; S3. Cool the melt to the second temperature plateau, add Al-Er master alloy and the remaining Al-Mn master alloy and Al-Cr master alloy, and hold at the temperature; S4. Cool the melt to the third temperature plateau, add Sr and Mg, and hold at that temperature; S5. Degas and filter the melt; S6. Vacuum die casting is performed on the processed melt. S7. Perform low-temperature stabilization treatment on the die-cast parts. The first temperature platform is 760℃~780℃, the second temperature platform is 710℃~725℃, the third temperature platform is 675℃~690℃, and the low-temperature stabilization treatment temperature is 300℃~340℃.
7. The method for preparing motor end caps from Al-Si-Cu die-cast aluminum alloy according to claim 6, characterized in that, In step S1, recycled material accounts for 15% to 35% of the total charge.
8. A method for preparing motor end caps from Al-Si-Cu die-cast aluminum alloy according to claim 6, characterized in that, The heat preservation time in step S2 is 8–20 min, the heat preservation time in step S3 is 10–18 min, and the heat preservation time in step S4 is 3–8 min.
9. A method for preparing motor end caps from Al-Si-Cu die-cast aluminum alloy according to claim 6, characterized in that, In step S5, Ar gas or Ar / N2 mixed gas is used for degassing, and the degassing time is 8 to 18 minutes. The filter is a ceramic filter plate with a porosity of 30 PPI to 50 PPI.
10. A method for preparing motor end caps from Al-Si-Cu die-cast aluminum alloy according to claim 6, characterized in that, In step S6, the vacuum degree of vacuum die casting is no more than 30 kPa, the low-speed injection speed is 0.2 to 0.8 m / s, the high-speed injection speed is 2.5 to 4.5 m / s, the boosting pressure is 65 to 110 MPa, and the mold temperature is 180℃ to 240℃; the low-temperature stabilization treatment time in step S7 is 2 to 6 h.
Citation Information
Patent Citations
High-strength and high-toughness die-cast aluminum alloy and preparation method thereof
CN108034870A
High thermal conductivity and high strength low-Si cast aluminum alloy and preparation method thereof
CN111485146A
Method for preparing regenerated ADC12 aluminum alloy from scrap aluminum
CN113278831A
Motor rear end cover
CN219268609U